Time-In-Cell 2019: A Snapshot of Restrictive Housing based on a Nationwide Survey of U.S. Prison Systems (2020)
This report provides a picture based on 2019 data from thirty-nine jurisdictions about the use of restrictive housing. For this analysis, we defined restrictive housing as holding individuals in a cell for an average of twenty-two hours or more a day for fifteen days or more. Through a nation-wide survey, we have gathered data enabling an understanding of the number of individuals held in solitary confinement, their demographic makeup, the duration of time that they spent in solitary confinement, and aspects of the rules governing that confinement. The collection of this information is a joint undertaking of the Liman Center at Yale Law School and the Correctional Leaders Association (CLA), formerly the Association of State Correctional Administrators (ASCA). Since 2012, the Liman Center and CLA have worked together on a variety of projects, several of which relate to restrictive housing.https://digitalcommons.law.yale.edu/amlaw/1025/thumbnail.jp